2021
DOI: 10.3390/foods10123033
|View full text |Cite
|
Sign up to set email alerts
|

Edible Aquatic Insects: Diversities, Nutrition, and Safety

Abstract: Edible insects have great potential to be human food; among them, aquatic insects have unique characteristics and deserve special attention. Before consuming these insects, the nutrition and food safety should always be considered. In this review, we summarized the species diversity, nutrition composition, and food safety of edible aquatic insects, and also compared their distinguished characteristics with those of terrestrial insects. Generally, in contrast with the role of plant feeders that most terrestrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 136 publications
0
15
0
Order By: Relevance
“…(Figure 1a) is not only rich in protein, fat, carbohydrate and ash, but it is also excellent in phosphorus, iron, copper, calcium and contains all essential amino acids for human consumption (Maneechan and Prommi, 2021). Similar to that, the nymph of damselfly Lestes praemorsus was also found to have good amount of protein and rich with different kinds of essential acid amino (Zhao, 2021). According to Macadam and Stockan (2017), there are about 58 edible species of Odonata recorded worldwide.…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…(Figure 1a) is not only rich in protein, fat, carbohydrate and ash, but it is also excellent in phosphorus, iron, copper, calcium and contains all essential amino acids for human consumption (Maneechan and Prommi, 2021). Similar to that, the nymph of damselfly Lestes praemorsus was also found to have good amount of protein and rich with different kinds of essential acid amino (Zhao, 2021). According to Macadam and Stockan (2017), there are about 58 edible species of Odonata recorded worldwide.…”
Section: Introductionmentioning
confidence: 73%
“…Insects such as dragonflies and damselflies are used as food and play a significant part in the diets of the many ethnic communities worldwide (Mozhui et al, 2020). In general, dragonflies are great sources of protein (45% to 76%) (Ordoñez-Araque et al, 2022), which is more than that of traditional meat from animals (Zhao et al, 2021). Data on the protein content (Table 1) showed that Sympetrum species contains the highest amount of protein (76.75%) (Narzari and Sarmah, 2017), whereas Pantala sp.…”
Section: Proximate Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aquatic insects, although consumed by many, feature less often in research on human entomophagy. This is why the paper by Min Zhao et al [ 31 ] is important. The authors reviewed what is known about edible aquatic insects and pointed out that the vast majority of the latter, in contrast to the phytophagous terrestrial edible species, are carnivorous.…”
mentioning
confidence: 99%